The impact of nutrient deficiency on the structure of soil microbial communities within a double-cropping system - Yang, Rulan; Sun, Zheng; Gong, Yu; Zhou, Peng; Zhang, Xinping; Wang, Jie; Dong, Qiang; Gao, Fei (Frontiers in Plant Science, 2025)
In the North China Plain, it is common for farmers to regularly clear crop residues from their fields. The prevalent practice of fertilization in this region continues to depend heavily on the use of compound fertilizers. Howere , long-term single fertilizer application has become the norm in the present agricultural production, which not only destroys the crop rotation system but also negatively affects the soil environment and crop yields. The current knowledge of how nutrient deficits affect the microbial community structure in double-cropping systems is still limited. To clarify the specific response of soil microorganisms to the absence of key nutrients in the ecosystems of the annual double cropping system, this study investigated how the lack of essential nutrients affected the diversity, abundance, and functional dynamics of microorganisms in the soil, and designed five treatment methods: (1) CK, nofertilizer treatment; (2) NPK, adequate nitrogen fertilizer, phosphorus fertilizer, and potassium fertilizer treatment; (3) PK, nitrogen deficiency treatment; (4) NK, phosphorus deficiency treatment; and (5) NP, potassium deficiency treatment. The results showed that in two growing seasons, NPK treatment increased the yields of wheat and corn by 16.9% and 27.0%, respectively, while NK and NP treatments increased by 13.4%, 5.4%, 25.0%, and 17.9%, respectively, and the total annual yield increased by 21.1%. In addition, NPK treatment promoted the microbial diversity and abundance of wheat and maize, and balanced fertilization provided more comprehensive nutritional support for crops. Compared to other nutrient-deficient treatments, NPK treatment substantially increased the abundance and functional diversity of soil bacterial and fungal communities (p<0.05). The structure and abundance of soil microbial communities are significantly correlated with soil physicochemical factors that involve organic matter, pH, potassium content, phosphorus, and nitrogen levels. pH is the primary environmental factor influencing the diversity of soil microbial communities.